Potensi Kriminal Cyber Crime pada Meme Pejabat Politik Indonesia: Kajian Linguistik Forensik - Essy Yunita Windari; Syahrul Ramadhan; Amril Amir (Imajeri: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This article aims to describe the findings of forensic linguistic analysis of language expressions on meme potentially used in cybercrime crimes. The linguistic form of the meme, including words, phrases, and clauses, serves as a data source. Three political-themed memes were chosen as representative examples. Data from Internet communication channels. The data is subsequently evaluated syntax, semantic, pragmatic, and forensic components. The results of forensic language-based analysis showed that the three meme could be involved in online criminal activity. This violation is possible, as evidenced by the offensive actions of expressive and persuasive illusion. The use of linguistic machinism such as “the president is useless”, “sell only”, “stupid”, etc. is one type of insult. Obviously, the comment was addressed to Jokowi and Makruf Amin personally. At their respective site locations, these three meme are still available to the public. These three memes are potentially violated, and it could make the perpetrator violate Articles 27 and 45 of the ITE Act. In addition, Chapter XVI, Sections 310 to 321 of the Code of Criminal Procedures on Disgrace discusses the offence of pollution of good name.